The Effect of Health Education Using Poster Media on Mothers’ Knowledge Level About Toddler Malnutrition in the Working Area of Saigon Health Center, East Pontianak - Anggi Lestari, Aprilia; Fradianto, Ikbal; Tafwidhah, Yuyun (Syntax Corporation Indonesia, 2024)
Nutritional deficiencies in toddlers can lead to growth and development disturbances, one of which is the occurrence of malnutrition. One of the main factors contributing to malnutrition in toddlers is the lack of knowledge among mothers about the nutrition required for their children. To improve this knowledge, one of the efforts that can be made is through continuous counseling using educational media, such as posters that are visually designed to be appealing, thus being effective in the learning process. This study aims to determine the effect of health education using posters on mothers' knowledge about toddler malnutrition in the working area of Saigon Health Center in East Pontianak. This study uses a quantitative pre-experimental method with a one-group pretest-posttest design. A total of 45 respondents were selected using probability sampling with a cluster random sampling technique. Data analysis was conducted using the Paired sample t-test. The results showed that most of the respondents' children were aged ≤ 2 years (66.7%), with the highest level of maternal education being high school (42.2%), and the majority of respondents' ages ranged from 20 to 42 years, with an average age of 31.42 years. The results of the Wilcoxon test showed a p-value of 0.001, indicating a significant improvement in mothers' knowledge about toddler malnutrition after receiving health education using posters.